Who Can Get More Happiness? Effects of Different Self-Construction and Experiential Purchase Tendency on Happiness - Xie, Aili; Liu, Lianhua; Lyu, Shiqi; Wu, Lijuan; Pan, Wen Tsao (Frontiers in Psychology, 2022)
This study introduces the self-construction methods of consumers and the tendency characteristics of experiential purchase to study the effects of physical purchase and experiential purchase on wellbeing. The dependent self-builders obtain higher happiness from experiential purchase; however, the independent self-builders get higher happiness from physical purchase. Furthermore, consumers with a high purchase experience get higher happiness from experiential purchase. Consumers with high material consumption tendency get significantly higher happiness than physical purchase from experiential purchase. Consumers with high materialism tendency gain higher happiness in experiential purchase, which is in line with the expectations of self-construction and consumption theories. This study provides the first evidence for the impact of self-construction methods on wellbeing with different consumption choices.